The advent of system toxicology: aims and aspect of toxicogenomics - Mahmud, S. M. Neaz; Mahmud, Shahin; Tandra, Tamanna Tazrin; Kar, Antora; Shathy, Elia Jahan; Jahan, Nasreen (International Journal of Basic & Clinical Pharmacology, 2017)
Last fifty years a significant advancement has been established in biological science. It happened due to the discovery of gene, genome and genetic code, function of genes and mutation of genes. Through this, the scientists have discovered that genetic code is the building block and fundamental of all molecular activity in biological system. According to this, several molecular techniques have been established to prove molecular events, effects of chemical exposure within individuals and environment. For this evaluation, the necessary of toxicogenomics is crucial, that deals with the effects of chemical in changing the genetic pattern along with mutation into gene. Toxicogenomics also deals with transcription of proteins and metabolite profiling to investigate the interaction of genes and environment stress in disease. Toxicogenomics also described the altered expression of genes caused by mutation and chemical exposure that cause several disease and show toxicant functions in cell. The main objective of toxicogenomics is to remove this exposure and provide remedy of these toxical diseases. The use, application, correlation, combination and collaboration of different significant, major, modern biological fields like proteomics, transcriptomics, bioinformatics, microarray and several other molecular process is carried out by toxicogenomics that gradually evolving in systems toxicology. This review recovered the evolution and significant application of the different fields of toxicogenomics.